Forensic odontology: bridging justice and human rights - Acharya, Neha; Babu, N. Aravindha (International Journal Of Community Medicine And Public Health, 2025)
A crucial area of forensic science is forensic odontology, which applies dental knowledge to support legal and humanitarian investigations. In the late 19th and early 20th centuries, Dr. Oscar Amoedo—who is regarded as the father of forensic odontology-founded this field. This area is essential for human identification in criminal cases, accidents, and mass disasters; it helps law enforcement and gives families closure. Dental age estimate is one of its primary uses, producing age-related data with scientific accuracy for medical-legal and humanitarian applications. Age is estimated using a variety of techniques, which can be broadly divided into developmental, degenerative, radiographic, histological, periodontal, and combination approaches. Assessing tooth mineralization and eruption sequences, especially in youngsters, is part of developmental techniques. Degenerative methods assess age-related damage, including root transparency and tooth attrition. Cementum increment analysis is one of the imaging techniques used in radiography to evaluate the morphology of teeth and roots. Histological methods that analyze age-related tissue changes at the microscopic level include microradiography and histomorphometry. Alveolar bone density and structure are studied via periodontal techniques. Several indicators are integrated for increased accuracy in multidimensional and combination techniques. Through the integration of scientific methodologies with societal requirements, forensic odontology plays a vital role in promoting justice, identifying victims, and safeguarding vulnerable groups, including children, in humanitarian settings.